Perovskite catalysts for methane combustion: applications, design, effects for reactivity and partial oxidation. (2nd August 2019) - Bashan, Veysi; Ust, Yasin
Summary: This review underlines the importance of the developments in perovskite catalysts for methane combustion from the past up to the present. In this review, after a general and brief introduction to perovskites, the mechanisms of catalytic combustion of methane have been included. Moreover, current studies on perovskites have been summarized including the effects of substitutions, doped perovskites, perovskite preparation methods, and the effect of sulfur presence on perovskite catalysts. Besides, recent studies on perovskite oxides and phenomenon of oxygen (O2 ) deficiency, porous perovskite oxides, and nanostructured perovskites have been conducted. In addition, partial oxidation of methane (POM) has been reviewed. The loss of active component during the POM reaction can take place in the nickel catalyst, in particular. Since nickel has a lower melting point than noble metals and other active components, such as Co and Fe, in general, to deactivate nickel is easier. Compared with conventional structure, the porous structure with the unique morphology significantly enhances the catalytic activity through a much larger surface area (SA) and greater reactivity of the active sites. Furthermore, the monolithic nanoarrayed perovskite presents very good results in well‐defined faceted catalysts and takes part in porous channel hydrocarbon combustion. This review study is prepared as a guide to cover the profound knowledge of perovskite oxides catalysts, considering the methane combustion reaction mechanisms, and addresses prospective studies in this field for researchers. Abstract : In this review, we summarize the recent developments in perovskite catalyst for methane combustion. The effects of substitutions, doped Perovskites, perovskite preparation methods, and the effect of sulfur presence on perovskite catalysts have been examined. Besides, the phenomenon of oxygen deficiency, porous perovskite oxides, and nanostructured perovskites have been issued. In addition, partial oxidation of methane (POM) has been reviewed. Recent advances in catalytic materials and potential mechanisms will probably cause perovskite catalysts to show excellent activity in the near future.